Simulating value co-creation in digital agri-food platforms: An agent-based model of consumer–producer interaction in the organic vegetable market - Rini, Neneng Kartika; Deliana, Yosini; Wibowo, Kunto Adi; Trimo, Lucyana; Setiawan, Iwan; Sukmawani, Reny; Widianto, Sunu; Wulandari, Eliana (Edelweiss Applied Science and Technology, 2025)
This study explores how value co-creation (VCC) mechanisms shape consumer and producer engagement on digital platforms for organic vegetables using an Agent-Based Modelling (ABM) approach. It addresses key challenges such as trust issues, price sensitivity, and limited consumer participation. A virtual simulation was developed in NetLogo with diverse agents, including millennials, baby boomers, and organic producers, interacting across five scenarios: baseline, full VCC integration, high price sensitivity, trust shock, and enhanced co-learning. The model incorporates key dimensions of value co-creation, including co-design, co-learning, co-process, and co-service. Results indicate that full VCC integration enhances satisfaction, producer retention, and platform loyalty, with co-learning emerging as the most effective mechanism under difficult conditions. Although trust disruptions and price concerns negatively affect system behavior, adaptive platform features help reduce these impacts. Patterns such as behavioral convergence and reinforcing feedback loops were observed, underscoring the role of the platform as an adaptive facilitator. The study contributes to value co-creation theory in digital food markets and demonstrates the value of ABM in agricultural digital research. Practical implications include recommendations for participatory design features and strategies to strengthen trust. This research supports sustainable agriculture by offering a scalable framework for inclusive and resilient digital ecosystems.